Third Five Year Plan (1961-66) A Review Gujarat Staff - Planning Commission (Planning Commission, 1968)
Gujarat is situated on the west coast of India, between 20.1 and 24.7 degrees north latitude and 68. 4 and 74.4 degrees east longitude. The State is bounded by the Arabian sea in the west, Pakistan and Rajasthan deserts in the north west, Madhya Pradesh in the east and Maharashtra in the south. The plains in the State are drained by major rivers like Narmada, Tapi, Mahi, Sabarmati Bank and Saraswati and small rivers like Machhtu, Bhadar, Shetrunji and Damanganga etc.
Government of Gujarat General Administration Department
Government of Gujarat General Administration Department